LDL-oxidation, serum uric acid, kidney function and pulse-wave velocity: Data from the Brisighella Heart Study cohort. (15th June 2018) - Cicero, Arrigo F.G.; Kuwabara, Masanari; Johnson, Richard; Bove, Marilisa; Fogacci, Federica; Rosticci, Martina; Giovannini, Marina; D'Addato, Sergio; Borghi, Claudio; ,
Abstract: Background: Serum uric acid (SUA) and oxidized LDL (oxLDL) may be associated with arterial aging. The aim of our study was to evaluate the relationship between SUA, oxLDL and arterial stiffness in subjects with normal renal function and in patients with mild or moderate renal impairment. Methods: From the database of the 2012 Brisighella Heart Study, we compared age-matched adult, non-smoker subjects without cardiovascular disease and with normal renal function ( n  = 205), subjects with stage II chronic kidney disease (CKD) ( n  = 118) and subjects with stage III CKD ( n  = 94). All subjects underwent a determination of the LDL oxidative susceptibility, oxLDL levels, SUA and Pulse Wave Velocity (PWV). Results: By univariate analysis, PWV correlated with a large number of clinical, haemodynamic and metabolic parameters, including estimated glomerular filtration rate (eGFR) in subjects with normal renal function and in those with stage II or III CKD. Stepwise multiple regression analyses showed that in the presence of normal renal function or stage II CKD, the main predictors of PWV were age, systolic blood pressure (SBP), ox-LDL, apolipoprotein B and SUA ( p  < 0.05), while in the presence of stage III CKD only age, SBP and apolipoprotein B remained significant (p < 0.05). Conclusion: Both ox-LDL and SUA independently predicts PWV only in subjects with normal or mildly reduced renal function, but not in the subjects with more compromised eGFR. This study confirms the complex relationship of SUA with cardiovascular and metabolic disease in the patient with established renal disease. Highlights: Serum uric acid (SUA) and oxidized LDL (oxLDL) may be associated with arterial aging but their interaction is not clear. This effect could be partly related to the degree of residual renal function In our study, SUA independently predicts PWV only in subjects with normal or mildly reduced renal function. oxLDL remains an independent risk factor for PWV independent of eGFR